Propriedades tecnológicas das madeiras de Melia azedarach L., Cordia americana (L) Gottschling J. S. mill. e Parapiptadenia rigida benth submetidas à biodegradação - Machado, Sabrina Finatto (2016)
This research aimed to evaluate the technological properties of wood three forest species subjected to biodegradation. To this end, C. americana, P. rigida and M. azedarach trees belonging to a forest, located in Jaguari - RS, aged 32 to 45, were used. After cutting, the logs have been broken down into a central plank with 7.0 cm thick and 20.0 cm wide and following the specimens were made. So they were stored in a climatic chamber at temperature of 20 ° C and relative humidity of 65%, where they remained until the equilibrium moisture content. The installation of field trials took place in three distinct regions: Santa Maria, São Gabriel and Pelotas. Every 60 days, ten samples per treatment were taken in each region, which were placed in a climatic chamber under the same initial conditions and subjected to equilibrium moisture test (TU), density, weight loss, colorimetry, evaluation of the deterioration index, bending, hardness, chemical analysis and testing of accelerated decay in the laboratory. Based on the results it was observed the wood of C. americana, P. rigida showed better technological properties with respect to M. azedarach wood, with high durability when subjected to natural conditions of deterioration and highly resistant to the action of decay fungi. On the other hand M. azedarach wood did not show good durability when exposed directly in contact with the ground, with a significant reduction of their mechanical and physical properties.